2005
DOI: 10.1016/j.seizure.2005.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and knowledge of epilepsy among students in a Malaysian university

Abstract: The findings indicate a generally favorable level of awareness and knowledge of epilepsy among students at the university. Nevertheless, there is still a need to improve certain aspects of knowledge and understanding of epilepsy among university students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
65
4
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 17 publications
10
65
4
3
Order By: Relevance
“…90.0% of them knew high fever as a cause of seizure in the current study while only 67.3% in the Thailand study [8]. Interestingly, 83.5% of the students thought epilepsy was genetic in origin, similar to a report from a Malaysian study (67%) [19] and the Thailand study (50.0%) [8], although no more than 1-2% of cases are due to genetic disorders [18].…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…90.0% of them knew high fever as a cause of seizure in the current study while only 67.3% in the Thailand study [8]. Interestingly, 83.5% of the students thought epilepsy was genetic in origin, similar to a report from a Malaysian study (67%) [19] and the Thailand study (50.0%) [8], although no more than 1-2% of cases are due to genetic disorders [18].…”
Section: Resultssupporting
confidence: 73%
“…While none thought it is caused by any supernatural cause in a similar study from Thailand [8]. A significant proportion of respondents in other studies harbored supernatural associations as predisposing factors [17,18] despite medical evidence showing that epilepsy arises from a transient dysfunction in the brain [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some general inferences however can be drawn.Analysis of these studies revealed regional differences in KAPs which could be attributed to local factors, such as literacy, awareness about epilepsy, and category of study population. [28][29][30][31] Survey conducted on predominantly Malay population in Kelantan, Malaysia, (2000) found that respondents were familiar with epilepsy but many maintained a negative attitude and had poor knowledge on causation and treatment of epilepsy. 28 Another survey (2002) carried out among the university students in University Sains Malaysia indicated favourable level of awareness and knowledge of epilepsy but (70%) of students did not know the cause of epilepsy, 67% believed that it was acquired through inheritance and 5% thought that it was caused by evil spirits.…”
Section: Discussionmentioning
confidence: 99%
“…%80.3'ü nöbet esnasında nasıl yardım edileceğini bilmediğini belirtmiştir. [37] Malezya'daki üniversite öğrencilerine uygulanan ankette %60'ı, Burkina Faso'daki öğretmenlerin %7.7'si ve Ürdün'deki öğretmenlerin %45.2'si epilepsi hastalığının kalıtsal olduğunu belirtmiştir. [30,37,38] Bozkaya'nın çalışmasında da öğrencilerin dörtte biri epilepsinin bulaşıcı bir hastalık olduğunu düşünmüşlerdir.…”
Section: Discussionunclassified